(untitled) (Jurnal Ecosolum, 2023)
The Palopo City West Ring Road is included in the Malili Sheet which is in Salobulo Village, Wara Utara District, South Sulawesi Province with coordinates 2º59’32.10” - 2º58’41.10”S and 120º10’34.51” - 120º10’40 .49” East. This study aims to determine the potential for landslides based on rock characteristics and slope geometry using the exploratory method, namely conducting research directly in the field and laboratory testing. Data acquisition was carried out at 5 observation stations which indicated the potential for landslides to occur. The data obtained are rock characteristic data including, rock type, fresh color and weathered rock color, rock texture and rock structure, as well as sampling, while the slope geometry data collection includes, height and slope of the slope, as well as observing other supporting factors namely, the degree of weathering, the presence of joints, surface runoff and the condition of the land vegetation.The results of data analysis show that the Palopo City West Ring Road has the potential for landslides which are influenced by several causal factors, namely, the steep slope of the slope, dominated by basalt rock which has undergone a weathering process with a high level of weathering at stations 2, 4 and 5 and the level of weathering moderate at stations 1 and 3. In addition, the presence of joints at stations 1 and 2 is a supporting factor for the potential for landslides to occur at the study site.